2022
DOI: 10.18290/rpsych2022.0014
|View full text |Cite
|
Sign up to set email alerts
|

Employee Entitlement: Is There A Universal Approach That We Can Use in the Organizational Settings?

Abstract: Employee entitlement has been studied over the years, yet few human resources management scholars and managers expected it to be a common phenomenon, especially among younger employees. Therefore, there is a need for deeper insight into employee entitlement as it has been analyzed in different ways over the last years. Due to dynamically and rapidly changing organizational settings, employee entitlement should be considered as a context-dependent variable. Additionally, it does not have to be perceived explici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…They concluded that a sense of entitlement can be an important coping resource (Brant & Castro, 2019;Confino et al, 2023;George-Levi & Laslo-Roth, 2021). Piotrowski and Żemojtel-Piotrowska (2009) proposed a model of the sense of entitlement consisting of three forms: active entitlement, based on the protection of one's self-interests; passive entitlement, which focuses on the conviction that institutions and organizations are obligated to satisfy one's needs, and revenge entitlement, based on the protection of one's self-interests when they are threatened or violated. Out of the three, active entitlement seems to be a proactive and an agentic aspect of psychological wellbeing, and thus regarded as a resilience factor.…”
Section: Sense Of Entitlementmentioning
confidence: 99%
“…They concluded that a sense of entitlement can be an important coping resource (Brant & Castro, 2019;Confino et al, 2023;George-Levi & Laslo-Roth, 2021). Piotrowski and Żemojtel-Piotrowska (2009) proposed a model of the sense of entitlement consisting of three forms: active entitlement, based on the protection of one's self-interests; passive entitlement, which focuses on the conviction that institutions and organizations are obligated to satisfy one's needs, and revenge entitlement, based on the protection of one's self-interests when they are threatened or violated. Out of the three, active entitlement seems to be a proactive and an agentic aspect of psychological wellbeing, and thus regarded as a resilience factor.…”
Section: Sense Of Entitlementmentioning
confidence: 99%